Report and resolves in relation to the commercial intercourse between the United States and the British provinces of Nova Scotia and New Brunswick (Document (Maine. Legislature. House of Representatives), 1838)
March 15, 1838 Report and resolves of the Joint Select Committee on the need to request Maine's senators and representatives in Congress to seek negotiations with Britain so that Nova Scotia and New Brunswick ports be allowed for ports of delivery and reception for the United States.